Credit Management Practices and Bank Performance: A Case of Nepalese Commercial Banks - Mahato, Minu (Nepalese Journal of Finance, 2025)
The study examines the effect of credit management practices on the performance of Nepalese commercial banks. Return on assets and return on equity are selected as the dependent variables. The selected independent variables are capital adequacy ratio, non performing loan ratio, client appraisal, credit term, bank size, liquidity ratio. The study is based on primary as well as secondary data. The primary source of data is used to assess the opinions of the respondents regarding client appraisal and credit terms in context of Nepalese commercial banks. To achieve the purpose of the study, structured questionnaire is prepared. Similarly, secondary data were collected for the study period from 2015/16 to 2020/21, leading to a total of 179 observations. The secondary data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and the effect of credit risk management on the performance of Nepalese commercial banks. The study showed that capital adequacy ratio has a positive impact on return on assets and return on equity. It means that an increase in capital adequacy ratio leads to increase in return on assets and return on equity. Similarly, non-performing loan has a negative impact on return on assets and return on equity. It means that an increase in non-performing loans leads to a decrease in return on assets and return on equity. Moreover, client appraisal has a positive impact on return on assets and return on equity. It means that increase in credit risk leads to increase in return on assets and return on equity. Furthermore, credit term has a positive impact on return on assets and return on equity. It indicates that better credit term leads to an increase in return on assets and return on equity. Similarly, bank size has a positive impact on return on assets and return on equity. It means that greater bank size lead to an increase in return on assets and return on equity. Likewise, liquidity ratio has a positive impact on return on assets and return on equity. It means that a better liquidity ratio leads to an increase in return on assets and return on equity in Nepalese commercial banks.